Методичні підходи до оцінки впливу екологічних факторів на ефективність інвестицій - Штефан Н. М.; Соляник Л. Г.; Гончарук А. М. (НТУ "ДП", 2023)
Результати. У статті висвітлені питання удосконалення критеріїв оцінки економічної ефективності інвестиційних проєктів у відповідності до вимог сучасних умов господарювання і життєдіяльності людства в цілому, надано рекомендації щодо врахування впливу екологічних факторів при визначенні економічної ефективності інвестиційних проєктів. Results. The article highlights issues related to the improvement of criteria for assessing the economic efficiency of investment projects in accordance with the requirements of modern economic conditions and the life of humanity as a whole, recommendations are provided in the field of taking into account the influence of environmental factors when determining the economic efficiency of investment projects.
Methodological approaches to assessing the impact of environmental factors on the efficiency of investments
Keywords: економічна ефективність інвестицій; екологічні фактори; оптимальна структура прибутку; economic efficiency of investments; environmental factors; optimal profit structure